The South China Sea is not a mini-Atlantic: plate-edge rifting vs intra-plate rifting - Wang, Pinxian (Natl Sci Rev, 2019)
The South China Sea, as ‘a non-volcanic passive margin basin’ in the Pacific, has often been considered as a small-scale analogue of the Atlantic. The recent ocean drilling in the northern South China Sea margin found, however, that the Iberian model of non-volcanic rifted margin from the Atlantic does not apply to the South China Sea. In this paper, we review a variety of rifted basins and propose to discriminate two types of rifting basins: plate-edge type such as the South China Sea and intra-plate type like the Atlantic. They not only differ from each other in structure, formation process, lifespan and geographic size, but also occur at different stages of the Wilson cycle. The intra-plate rifting occurred in the Mesozoic and gave rise to large oceans, whereas the plate-edge rifting took place mainly in the mid-Cenozoic, with three-quarters of the basins concentrated in the Western Pacific. As a member of the Western Pacific system of marginal seas, the South China Sea should be studied not in isolation on its origin and evolution, but in a systematic context to include also its neighboring counterparts.